The Role of Bartenders in Handling Beverage Orders at D'Nest Bar & Grill at Crown Vista Hotel Batam - Syafruddin Rais (Program Studi Hospitality dan Pariwisata, 2018)
ABSTRACTDue to the important of bar in giving beverage service, a bar is required for having an operational standard procedure in giving the service to the guest so that each guest will get the same service without any distinction. It is very helpful in making the service being successful so it is expected that the guests will get what they expect and avoid complaint. So in this paper, the author interests to conduct a research about the way of Bartenders in handling the beverages’ orders made by guests in D’Nest Bar and Grill Crown Vista Hotel.Type of data that will be used in this research are Qualitative data, data which is not containing numbers and can’t be counted. The data can be described in a detail and clear form. The data includes an overview of Vista Hotel and interview result which conducted with the bartender and guest. Quantitative data, data in numbers form which can be calculated or processed mathematically and statistically for drawing a conclusion. The taken data comes from the processed questioners about the guests’ opinion toward bartender service in handling beverages’ order. Data collecting technique in this research the author uses probability samples. According to Indriantoro and Supomo (1999:122), each population has the same probability to be taken as a sample. A representative sample is shown by an estimating statistic sample toward population parameter accurately and precisely. By the limitation of time, energy and cost, the author distributes the questioners of 70 respondents by the result of 2% Indriantoro and Supomo (1999:125) the number of the guest of D’Nest Bar and Grill Crown Vista hotel Batam.Data analysis technique this research is based on descriptive analysis, such as by describing, explaining the problem completely, and the obtained questioners which relates to the research problem during the research is conducted.Keywords: Bartender, ordering, beverage